On wings of moonlight : Elliot R. Wolfson's poetry in the path of Rosenzweig and Celan - Galli, Barbara E. (Barbara Ellen), 1949- (McGill-Queen's University Press, 2007)
Elliot R. Wolfson is the author of several critical books on medieval Jewish mysticism. On Wings of Moonlight focuses on the poetic nature of Wolfson's works through an exploration of his poems, many of which appear in Pathwings: Philosophic and Poetic Reflections on the Hermeneutics of Time and Language. Barbara Galli argues that Wolfson's poems resonate with a kabbalistic worldview that is also reflected in his scholarly work and personal life.